Relationship between despotic leadership, psychological contract breach, perception of injustice and work engagement: the mediating role of perception of job insecurity - Jabeen, Riffut (2022)
The global financial crisis has triggered an economic recession with a significant impact on human resources. Pakistani banking institutions are not exempted from such business consequences. In this context, a study was conducted on six big banks in Pakistan with significant contributions to economic activities. The study aims to examine the effect of despotic leadership, perception of injustice, and psychological contract breach on employees’ work engagement. The mediating role of job insecurity perception on these relationships is also investigated. Data collected from 625 employees using the judgmental sampling technique were analyzed using Structural Equation Modeling (SEM) technique in AMOS 24.0 software. The results revealed that despotic leadership, perception of injustice, and psychological contract breach negatively influenced the employees’ work engagement. Besides, the perception of job insecurity partially mediates these relationships. The study concentrates on the psychological process of employees to cope with the stressful environment created by despotic leaders, injustice, and breaches in the organization using the lens of conservation of resources. The study also empirically supports the conservation of resource (COR) theory and enriches the body of knowledge by integrating leaders’ behaviors and employee perceptions and outcomes based on these perceptions. Through mediation analysis, the study has provided a mechanism to identify the effects of despotic leadership on work engagement. The study has practical implications for the Human Resources (HR) departments in decision-making about leadership orientations or training their leaders. HR departments should effectively review their recruitment policies, procedures and performance appraisals to establish better work engagement.